POTENSI ESTROGENIK KOMBINASI EKSTRAK ETANOL 70% HERBA KEMANGI (Ocimum americanum) DAN BUAH ADAS (Foeniculum vulgare) PADA TIKUS PUTIH (Rattus norvegicus) BETINA PRE-MENOPAUSE - Effendi, E. Mulyati; Maheshwari, Hera; Husna, Mar’atul (Fakultas Matematika dan ilmu pengetahuan Alam. Universitas Pakuan.)
At the end of their fertile phase, female under go menopause state where ovaries cease to produce egg cells permanently, causing follicle to stop producing estrogen. The degradation of estrogen concentration in blood has significant undersirable influences on the structure and function of other organs. Some plants believed to have potential estrogenic effect based on several research are herb basil (Ocimum americanum L.) and fennel fruit (Foeniculum vulgare Mill.). This research armed to find out the estrogenic potency and synergic or antagonictic effect of 70% ethanol extract of herb basil and fennel fruit on pre-menopause female rats. Twenty pre-menopause female rats are divide into 5 groups and tested with whitten effect method. Group I as positive control is given peroral ethynil estradiol with 9x10-3g/200g BB, group II as negative control is given peroral CMC-Na 0,5%, group III is given peroral 70% ethanol extract of basil herb 0,35g/200g BB and fennel fruit 0,0725g/200g BB, group IV is given peroral 70% ethanol extract of herb basil 0,35g/200g BB and fennel fruit 0,145g/200g BB and group V is given peroral 70% ethanol extract of herb basil 0,7g/200g BB and fennel fruit 0,0725g//200g BB. The result shows that administration of 70% ethanol extract of herb basil 0,7g/200g BB and fennel 0,0725g/200g BB gave the most significant effect as compared negative control and better than positive control in the improvement of estrous cycle length, the vascularisation of ovarium and uterus, and the increase in ovarium and uterus weight in female rats. Key words : Estrogenic potential, Herb basil, Fennel fruit, Pre-menopause